The Establishment Policy Model of Sale Value of Land Tax Objects and Rural and Urban Sector Buildings (NJOP PBB P2) in Medan - Abdul Kadir; Isnaini Isnaini; Nina Angelia (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study focuses on explaining how the policy for determining the Sale Value of Land and Building Tax Objects for Rural and Urban Land and Building Tax (NJOP PBB-P2) is an effort to increase the regional revenue (PAD) of Medan City. The explanation of this study is built based on a qualitative method with a descriptive approach. The results of this study indicate that, the determination of NJOP PBB-P2 in Medan City has a variable NJOP PBB-P2 classification, also with a fluctuating value. Because the value is based on sectors and zones. The strategic location of the tax object will be of much greater value than in distant areas and is considered uneconomical. In the process of determining the PBB-P2 NJOP, the stages are, first, the process of collecting data on the NJOP PBB P-2 for Medan City. Second, the PBB P2 Assessment Process for Medan City. Third, the process of determining the NJOP PBB P-2 for Medan City. Fourth, the process of collecting PBB P2. In practice, the most dominant problem is the refusal of residents to pay taxes, arrears, differences in NJOP values between regions and even market values that do not match the selling price are problems that are always faced. This argument is caused by the negative image attached to the Medan City Government and the Agency in charge of collecting taxes which causes public distrust. So this study provides basic recommendations through a policy model in determining the NJOP PBB-P2 which is more just, accountable, transparent and democratic. This just, democratic policy model is seen from the dimensions of administrative modernization and the dimensions of citizen involvement. The orientation is to create a balance and healthy social relations between citizens and the government.